Transporte de umidade nos climas presente, passado e futuro sobre a América do Sul - Coutinho, Maytê Duarte Leal; Lima, Kellen Carla; Silva, Cláudio Moisés Santos e (Revista Brasileira de Geografia Física, 2013)
Aiming to verify whether the RegCM3 regional model can represent the climate of South America (SA), was analyzed the monthly average of rainfall in winter and summer, for the present climate (1991-2008). Then, it was evaluated the vertically integrated moisture flux for different climates, that’s it, the past (1961-1990), present (1991-2008) and future (2071-2100), in three areas of the AS: Northeast Brazil (NEB), Amazon (AMZ) and the La Plata Basin (LPB). The analyzes performed for the present climate, showed that in summer, the RegCM3 represents the rainfall pattern oriented in the northwest-southeast direction, characterizing the convergence zone of the South Atlantic (SACZ). However in winter, RegCM3 makes the Intertropical Convergence Zone (ITCZ) more confined meridionally in the continental region. In summary, the mistakes related to the SACZ and ITCZ seem to be important to explain the overestimation of precipitation at Amazon Central and west AS. Regarding the moisture flux was observed generally that the average flow of the AMZ and NEB provides most of the water vapor on the eastern edge, suggesting that the contributions of the trade winds of the North Atlantic and South are equally important to ingress of moisture during the summer and winter. Once the moisture transport was greater in the future climate in AMZ and NEB, compared with the past and present climate in both seasons. Regarding the LPB, it was observed that the region is humid in summer (presence of Low Level Jets) and dry in winter (Monsoon in SA). Objetivando verificar se o modelo regional RegCM3 consegue representar o clima da América do Sul (AS), foi realizado as médias mensais da precipitação e umidade específica no inverno e verão para o clima presente (1991-2008). Em seguida, avaliou-se o fluxo de umidade integrado verticalmente para diferentes climas, isto é, passado (1961-1990), presente (1991-2008) e futuro (2071-2100), em três áreas da AS: Nordeste do Brasil (NEB), Amazônia (AMZ) e Bacia do Prata (LPB). As análises realizadas ...